Stratigraphy and Depositional Model of the Chert Member of the Semanggol Formation, Kebun 500, Pokok Sena, Kedah - Mohammad, Mohamad Asyraf (2016)
The study presents the result of stratigraphy and depositional environment of Semanggol formation at an outcrop at Kebun 500, Pokok Sena, Kedah in northern Perak. Previous published research had established stratigraphic log and depositional model around Pokok Sena area but yet to explore on Kebun 500. Previous study also recorded occurrence of microfossils in few area around Northern Kedah region. Thus the objectives of this study is to investigate on the stratigraphy and to propose a depositional model of the exposed rock at Kebun 500, Pokok Sena Kedah. The study also includes a secondary objective which is to identify possible occurrence of microfossils to determine the age of the outcrop. Geological approach had been implemented throughout the study to produce a comprehensive outcome. The approaches include basic geological study of Kedah, fieldwork activity and lab analysis. The outcrop extends 100 m East-West with prominent bedding of interbedded chert and mudstone with occurence of structural related rocks in between. Generally the interbedded layers dipping eastward almost vertical. The outcrop also exhibits three transgressive event based on the thickness variation of chert and mudstone layers. The boundary of chert member and rhythmite member was also proposed in a lithology map around the study area. A submarine fan model is proposed as an analogue to explain the depositional environment of the exposed rock. Presence of radiolarian had also been identified in the thin section of chert sample.